Mechanisms of Penetration Enhancement and Transport Utilizing Skin Keratine Liposomes for the Topical Delivery of Licochalcone A - Wenfeng Wu; Zhuxian Wang; Yufan Wu; Huiyi Wu; Tingting Chen; Yaqi Xue; Yuan Wang; Cuiping Jiang; Chunyan Shen; Li Liu; Hongxia Zhu; Qiang Liu (Molecules, 2022)
Keratin liposomes have emerged as a useful topical drug delivery system given theirenhanced ability to penetrate the skin, making them ideal as topical drug vehicles. However, the mechanisms of the drug penetration enhancement of keratin liposomes have not been clearly elucidated. Therefore, licochalcone A(LA)-loaded skin keratin liposomes (LALs) were prepared to investigate their mechanisms of penetration enhancement on the skin and inB16F10 cells. Skin deposition studies, differential scanning calorimetry (DSC), attenuated total reflection-Fourier Transform Infrared Spectroscopy (ATR-FTIR), and skin distribution and intracellular distribution studies were carried out to demonstrate the drug enhancement mechanisms of LALs. We found that the optimal application of LALs enhanced drug permeation via alterations in the components, structure, and thermodynamic properties of the stratum corneum (SC), that is, by enhancing the lipid fluidization, altering the skin keratin, and changing the thermodynamic properties of the SC. Moreover, hair follicles were the main penetration pathways for the LA delivery, which occurred in a time-dependent manner. In the B16F10 cells, the skin keratin liposomes effectively delivered LA into the cytoplasm without cytotoxicity. Thus, LAL nanoparticles are promising topical drug delivery systems for pharmaceutical and cosmetic applications.